Enzyme-linked immunosorbent assay for detection of IgG against penicillins in children - Zhang Lei; Wang Yong-Ming; Shen Gang; Chen Bin-Yan (Acta Pharmacologica Sinica, 2016)
AIM: To establish an enzyme-linked immunosorbent assay (ELISA) for detection of IgG against penicillins and then investigate this antibody response in children. METHODS: Western blotting, ELISA, and hapten inhibition assay were used. RESULTS: Penicillins reacted with bovine serum albumin (BSA) to generate conjugate which was used as coating antigen (100 mg.L-1) in ELISA. A good correlation was found between absorbance (A) and dilutions of sample with a linear coefficient of 0.9918. Thirteen subjects who were clinically suspicious of penicillin allergy were tested for specific IgG by ELISA, 4 positive for benzylpenicillin, 1 for benzylpenicillin and piperacillin, and 3 for benzylpenicillin, piperacillin and ampicillin. CONCLUSION: An ELISA was successfully established and penicillin reactive IgG response in children was heterogeneous. IgG antibodies recognized benzylpenicillin molecule, degraded products and new antigenic determinant from conjugate. Cross reactions occurred among benzylpenicillin, ampicillin and piperacillin.